Quantitation of mast cells and collagen fibers in skin tags - El Safoury Omar; Fawzy Marwa; El Maadawa Zeinab; Mohamed Dalia (Wolters Kluwer Medknow Publications, 2009)
Background: Skin tags are common benign skin tumors usually occurring on the neck and major flexors of elder people. Aims: The aim of this study is to perform quantitation of mast cells and collagen fibers in skin tags and normal skin in diabetics and nondiabetics, to find a possible correlation between mast cells and collagen fibers in the pathogenesis of skin tags. Methods: Thirty participants with skin tags were divided into two groups (15 diabetic and 15 nondiabetic). Three biopsies were obtained from one anatomical site: A large skin tag, a small skin tag, and adjacent normal skin. Mast cells stained with Bismarck brown were counted manually in ten different fields of each section with magnification Χ1000 and the average count was correlated with the percentage of mean collagen area in five fields done by the image analyzer. Results: A statistically significant correlation between mast cell count and percentage of collagen mean area was detected in both studied groups (except in large skin tags of the nondiabetic group). Conclusion: The positive correlation between mast cell count and percentage of collagen mean area suggests the critical role of mast cells in the etiogenesis of skin tags through its interaction with fibroblasts.